The Chemistry of Sustainable Energy Conversion and Storage - Guanglin Xia (Molecules, 2022)
The long-term environmental side-effects and finite supply of fossil fuels, which dominate the energy resources in our daily lives, require a transition to renewable and clean energy resources [...]